DAMPAK KETIMPANGAN SOSIAL TERHADAP PENYELESAIAN KONFLIK AGRARIA DI KECAMATAN JATINANGOR: PERSPEKTIF PEMBANGUNAN EKONOMI LOKAL - Achmad Nur Sutikno (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2026)
This research aims to analyze the impact of land access inequality on inclusive and sustainable local economic development in Jatinangor District, Sumedang Regency. Massive land use conversion during 2020-2023 (residential +59.16%, forest -50.24%, vacant land +83.77%) has created significant land ownership inequality, with 47% of agricultural land converted to factories, malls, residential areas, and commercial properties. Using qualitative approach with case study design and 13 key informants, this research identifies five multidimensional impacts: (1) employment—farmer transition to informal sector with significantly lower wages, (2) income—inequality increases (Gini ratio 0.337), (3) access to capital—farmers limited access to formal credit and dependent on informal ijon system, (4) environmental sustainability—severe ecosystem degradation with clean water coverage only 6.5%, and (5) social conflict—persistent agrarian disputes with ineffective resolution mechanisms. The research finds that economic development in Jatinangor is non-inclusive because benefits are only enjoyed by external actors (investors, educational institutions) while local farmers experience continuous marginalization. Integration of Inclusive Development Theory (Stiglitz), Land Tenure Theory, and Agrarian Conflict Theory demonstrates that land inequality hampers sustainable economic growth. The research recommends a holistic approach: agrarian reform, land conversion regulation, local economic empowerment, participatory conflict resolution mechanisms, and development planning based on inclusion principles. Keywords: land inequality, inclusive economic development, land use conversion, Jatinangor, agrarian conflict.